Fifty years of the supreme court of India its group and reach - Verma, S K (Ed.); Kusum (New Delhi Oxford University Press, 2000)
Fifty years of the supreme court of India,a commemorative volume, looks at fifty eventful years of the open court of justice. It takes stock of the contribution of the Supreme Court of India in shaping the law of India. The essays comprehansively cover al
Keywords: Constitutional courts-India; Courts-India; Law-India